ENHANCING PUBLIC SERVICE EFFICIENCY: A CASE STUDY-BASED PROCESS CAPABILITY ASSESSMENT IN SURABAYA - Anityasari, Maria; Sonhaji, Agus Imam; Akbar, Reza Aulia; Kusumawardani, Rindi; Indrawijaya, Rivaldo (JEMIS (Journal of Engineering & Management in Industrial System), 2025)
The application of lean six sigma in the manufacturing industry, particularly with regard to productivity enhancement, waste reduction, and production process efficiency, has gained greater recognition. Furthermore, the fundamental ideas of this field are highly applicable and could be used in the service industry, including public services offered by governmental organizations. In order to meet community needs, public services like those provided by Surabaya City's Regional Apparatus Organization (RAO) are crucial. The community, as users of public services, has no other options, so the quality of service provided by government agencies is the only hope, in contrast to the optional and competitive private sector services. These public services rely on the abilities and dependability of their personnel in addition to effective systems. In Indonesia and many other developing countries, these issues still exist. This study employed process capability analysis to evaluate 279 licensing and non-licensing services provided by 17 Regional Apparatus Organizations (RAOs) in the City of Surabaya over the previous 9 months. Sixty-three out of 279 services (22.6%) were below the level of sigma and that is smaller than 3σ, meaning there was inconsistency process performance capability against to average threshold value in Indonesia. This indicates that there is further room to enhance the operational systems as well as develop HR professional skills. It is hoped that this approach will tackle the root cause of the problem, and help drive creation of more reliable, effective and efficient services delivered fairly to all stakeholders.